The tribological behaviors of core‐shell n‐octadecane@TiO2/epoxy composites. Issue 11 (13th August 2020) - Zhao, Gengrui; Wang, Honggang; Ren, Junfang; Chen, Shengsheng; Gao, Gui; Wang, Na; Yang, Yawen
Abstract: In this work, the n ‐octadecane@TiO2 particles with core‐shell structure were successfully prepared via a sol‐gel method in an oil‐in‐water (o/w) emulsion. The resultant core‐shell particles were incorporated into epoxy matrix to prepare composites. Compared with pure epoxy and TiO2 doped epoxy, the incorporation of n ‐octadecane@TiO2 reduced the friction coefficient (COF) and wear rate of epoxy. According to the systematical investigation of the wear tracks on three samples and scars on their friction antithesis balls, it was speculated that the antifriction effect of core‐shell additives on composites were mainly attributed to the mixture formed by the crushed n ‐octadecane@TiO2 . The mixture not only backfilled the tearing‐like cracks on worn face generated by fatigue wear, but also promoted the formation of transfer film. Abstract : The incorporation of core‐shell n ‐octadecane@TiO2 particles improved the tribological properties of epoxy by backfilling the tearing‐like cracks on worn face and promoting the formation of transfer film.